Patterns of change in Malawi’s economy under sector-focused investment strategies: Results of scenarios run through 2030 using an economy-wide model for Malawi - Benson, Todd; Hartley, Faaiqa (International Food Policy Research Institute, 2020)
Malawi’s economic future is dependent upon a transformation of the economy that will involve increased economic productivity overall and considerable movement of labor and capital out of agriculture and into manufacturing and services. A dynamic Computable General Equilibrium model of the economy of Malawi was used to better understand the development gains that would be realized by 2030 through significantly increasing separately the productivity of each of the three sectors of the Malawian economy – agriculture, industry, and services. The scenarios run in the model involved increasing by 20 percent from current levels the annual growth rate in total factor productivity for each of the three sectors. The results show important trade-offs in the choice of which sector should receive emphasis in any economic development strategy. A services-led strategy would result in higher economic growth overall and broadly rising incomes, contributing the most to a structural transformation of the Malawi economy. However, the principal beneficiaries of increased investment to improve productivity in the services sector will be better-off households. In contrast, an agriculture-focused strategy would better meet the needs of the poor and their access to food, but would result in continued lagging growth for Malawi’s economy and many poorer households continuing to be unable to obtain sufficient income to exit their poverty and realize much better lives for themselves and their children. The industrial sector currently is much smaller than either the agriculture or services sectors, particularly in terms of employment, so significant increases in productivity growth in industry results in smaller benefits overall than comparable increases in agriculture or services.